Gender-based crimes against women in Katsina State, Nigeria: Patterns, determinants, and institutional responses - Muhammad Abdullahi Maigari; Muhammad Tasiu Dansabo; Auwal Ibrahim Abubakar; Alma Vorfi Lama (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2025)
Gender-based crimes against women in Katsina State occur at alarming levels and are systemically entrenched amid armed conflict. Extreme poverty, patriarchal norms, and weak legal protection create spaces of impunity for perpetrators, while inadequate institutional responses exacerbate women’s vulnerability and silence survivors. The aim of this study is to examine the structural factors underlying violence, the dominant forms of violence, and the implementation gaps in gender-based violence (GBV) protection policies in Katsina State, Nigeria. This study employs Interpretative Phenomenological Analysis (IPA) with in-depth interviews conducted with 14 survivors and key informant interviews. The data were thematically analyzed using source triangulation, member checking, and reflexivity to ensure validity. Three key findings: (1) structural factors: poverty, economic inequality, internal displacement, patriarchal norms, with most vulnerable groups; (2) dominant violence: rape, survival-based sexual exploitation, economic neglect by husbands, forced marriage, physical and psychological violence; (3) government adopted Child Rights Act, VAPP Act, GBV centers, but implementation constrained by weak law enforcement, poor coordination, limited rural access, cultural norms sustaining impunity. This study concludes violence against women in Katsina State is driven by poverty, patriarchy, and displacement, dominated by rape, sexual exploitation, and forced marriage, while weak policies and impunity sustain it. This study contributes by strengthening structural feminist and intersectionality perspectives and proposes an ecosystem model that simultaneously addresses economic neglect, cultural norms, and the roles of religious leaders.